Moderating roles of green technologies and trade diversification in resource-driven ecological pressures: evidence from G-20 economies using a panel MMQR approach - Li, Shuai; Du, Zhizhou (Frontiers in Environmental Science, 2026)
The ecological consequences of natural resource dependence and energy exploitation are drawing increasing global concern, particularly under the accelerating pressures of climate change. This study explores the direct and moderating effects of trade openness, trade diversification, and environmental technologies on the relationship between natural resource rents and ecological sustainability in G-20 economies from 1990 to 2023. Employing the Method of Moments Quantile Regression approach, the analysis uncovers heterogeneous impacts across the distribution of the ecological footprint. The results indicate that natural resource rents significantly intensify ecological pressures, with stronger effects observed in highly polluted economies than in cleaner ones. Moreover, greater diversification in resource extraction is found to exacerbate environmental degradation, rather than mitigate it, by broadening the scale of resource use. In contrast, environmental technologies consistently and robustly reduce ecological footprints across all quantiles, underscoring their critical role in promoting sustainability transitions. Trade openness further supports ecological sustainability by amplifying the positive effects of environmental innovation while moderating the negative impacts of resource dependence. Robustness checks using Granger causality analysis confirm bidirectional links between ecological footprint, natural resource rents, diversification, and environmental technologies, while GDP and trade openness display unidirectional causal effects. These findings emphasize that reducing dependence on resource rents, expanding renewable energy adoption, and accelerating the diffusion of clean technologies are essential strategies for G-20 nations to align economic growth with long-term ecological sustainability.